DIGITAL TRANSFORMATION OF THE ECONOMY OF UZBEKISTAN - Saidova , Oygul Khayrulloevna (Innovative Development in Educational Activities, 2023)
In the era of rapid technological advancement, Uzbekistan stands at the forefront of digital transformation, reshaping its economic landscape. This article delves into the profound changes catalyzed by digitalization, exploring how emerging technologies are fostering innovation, efficiency, and competitiveness within the nation’s economic framework. From the integration of smart technologies in industries to the government’s digital initiatives, the narrative unfolds the multifaceted journey of Uzbekistan towards a tech-driven economy. Join us in unraveling the digital tapestry that is propelling Uzbekistan into a new era of economic prosperity.